Government Strategy to Encourage MSME Tax Compliance through Digitalization - Dicky Rachmat Gunawan (Sean Institute, 2025)
This study aims to analyze the government's strategy to encourage tax compliance among Micro, Small, and Medium Enterprises (MSMEs) through the use of digitalization. The research background is based on the low level of tax compliance among MSMEs, which is influenced by limited understanding of regulations, complex administrative processes, and limited access to information. The research method used is qualitative with a descriptive approach, through literature review, policy analysis, and secondary data from official publications related to MSME taxation and the digitalization of public services. The results show that the government's tax digitalization strategy, through various services such as e-Filing, e-Billing, e-Registration, and MSME-specific applications, has proven effective in providing convenience, efficiency, and transparency in tax reporting and payment. However, its implementation still faces challenges such as the digital literacy gap, limited technological infrastructure in certain regions, low tax and financial literacy, difficulties adapting to new systems, as well as data security issues and resistance from some MSMEs. Therefore, the success of this strategy depends heavily on the synergy between technology enhancement, ongoing education, data protection, and a persuasive approach to build taxpayer awareness and trust.